2016
DOI: 10.1007/s10964-016-0442-1
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Oxidase A (MAOA) and Catechol-O-Methyltransferase (COMT) Gene Polymorphisms Interact with Maternal Parenting in Association with Adolescent Reactive Aggression but not Proactive Aggression: Evidence of Differential Susceptibility

Abstract: To date, whether and how gene-environment (G × E) interactions operate differently across distinct subtypes of aggression remains untested. More recently, in contrast with the diathesis-stress hypothesis, an alternative hypothesis of differential susceptibility proposes that individuals could be differentially susceptible to environments depending on their genotypes in a "for better and for worse" manner. The current study examined interactions between monoamine oxidase A (MAOA) T941G and catechol-O-methyltran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…In a recent review, the COMT gene was highlighted as one of the four most studied genes related to dopamine and serotonin pathways in association with aggression-related phenotypes 21 . Recent GxE studies have shown that COMT genotypes may modify the sensivity to environments that confer either risk or protection for aggressive behavior 22 23 24 .…”
mentioning
confidence: 99%
“…In a recent review, the COMT gene was highlighted as one of the four most studied genes related to dopamine and serotonin pathways in association with aggression-related phenotypes 21 . Recent GxE studies have shown that COMT genotypes may modify the sensivity to environments that confer either risk or protection for aggressive behavior 22 23 24 .…”
mentioning
confidence: 99%
“… Note: Female, nonshy individuals, and nonVVG were coded as 0; male, shy individuals, and VVG were coded as 1; Pearson correlation is equivalent to the t test effect (Zhang, Cao, Wang, Ji, & Cao, ).…”
Section: Resultsmentioning
confidence: 99%
“…Parenting behaviors have been found to interact with genes to affect human traits like creativity [24], depression [25], aggression [26], externalizing behavior [27], self-control [28], as well as EF [16,17]. Researchers have proposed that parenting behaviors likely influence the way children cope with stress, resulting in epigenetic changes in the HPA axis such as glucocorticoid receptor expression [29] or in the neurotransmitter systems such as dopamine, oxytocin, and serotonin [30].…”
Section: Discussionmentioning
confidence: 99%